Exploring the relationship between co-worker and supervisor support, self- confidence, coping skills and burnout in residential aged care staff - Yin Siu Low; Sunil Bhar; Won Sun Chen (BMC, 2022)
Abstract Background Staff working in residential aged care facilities face unique challenges and stressors in their workplaces which increase their risk for occupational burnout. Burnout in this workforce results in low job satisfaction, increased levels of absenteeism and poor retention rates. Given Australia's ageing population and the demand for residential aged care staff, it is imperative to explore predictors of burnout in this cohort in order to help staff prevent and manage burnout. Methods This study examined the extent to which co-worker and supervisor support, self-confidence and adaptive coping skills predicted burnout among residential aged care staff, after controlling for staff demographics, organisational climate and work patterns. One hundred and thirty three residential aged care staff across Australia were surveyed using online questionnaires measuring levels of co-worker and supervisor support, self- confidence, adaptive coping skills and burnout. Results Regression analyses indicated that, overall, co-worker and supervisor support, self-confidence, and adaptive coping predicted each dimension of burnout (emotional exhaustion, depersonalization and personal accomplishment). After controlling for covariates and other predictors: confidence significantly predicted all three dimensions; support significantly predicted emotional exhaustion and depersonalization, and adaptive coping significantly predicted emotional exhaustion. Conclusion These findings suggest that co-worker and supervisor support, self- confidence and adaptive coping skills need to be addressed to prevent and manage occupational burnout for residential aged care staff in Australia.